Ensino não presencial emergencial: uma visão de professores do ensino superior - Evangelista, Luiz Felipe Ossick (Universidade Federal de São Carlos, 2023)
The COVID-19 pandemic prevented the implementation of in-person classes across the country. Through the Emergency Remote Teaching Program (ENPE), UFSCar was able to maintain its academic functions. However, due to the remote learning modality, ENPE had a significant impact on the execution of classes. The aim of this study is to understand the perspectives of professors from the Biological Sciences course at UFSCar – São Carlos campus – regarding the processes of implementing remote teaching during the COVID-19 pandemic. The research was conducted using a qualitative approach, with semi-structured interviews conducted with faculty members who taught practical classes during the ENPE semesters. The overall results are quite comprehensive. Despite the lack of a governmental plan to support educational institutions, the university did what it could to assist educators in their work. Although there was a general plan developed by the university, it was not able to address all the specificities of the process. Therefore, each faculty member decided, based on their own experiences, how to adapt their classes according to their teaching methodology. By analyzing the professors' statements, it was possible to infer the choices and challenges they faced in adapting practical classes.
Emergency remote non-presential teaching: a perspective from higher education teachers
Keywords: Ensino remoto; Visão de professores; Aulas práticas; Metodologias; Remote teaching; Professors' perspectives; Practical classes; Methodologies; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM